Systematic review of the application of the Kidney Failure Risk Equation and Oxford classification in estimating prognosis in IgA Nephropathy - M. P. Toal; R. Fergie; M. P. Quinn; C. J. Hill; C. O’Neill; A. P. Maxwell (Systematic Reviews)
Abstract Background IgA nephropathy (IgAN) is the most common primary glomerulonephritis in the world and is an important cause of chronic kidney disease (CKD) and kidney failure. Outcomes are heterogeneous, and accurate risk stratification is important to identify the highest risk individuals for treatment and to help prevent disease progression. The Oxford classification (OC) is an internationally adopted standard for renal biopsy reporting in IgAN, which measures the degree of histological abnormalities and predicts prognosis. The kidney failure risk equation (KFRE) was developed to predict kidney failure in all causes of CKD and has been shown to be highly accurate across diverse etiologies. This review aimed to compare the KFRE with formulae incorporating the OC in accurately determining the risk of kidney failure in IgAN. Methods A systematic review was conducted in accordance with the Cochrane library guidelines and PRISMA statement for reporting of systematic reviews. Studies comparing the accuracy of the KFRE with the OC in predicting disease progression and kidney failure in IgAN were evaluated. The search strategy and analysis were performed independently by two reviewers. Studies that were eligible for inclusion compared the KFRE with any tool incorporating the OC in a cohort of individuals with IgAN. Eligible outcomes were reduction of estimated glomerular filtration rate (eGFR) or end-stage renal disease (ESRD), and prognostic tools were required to assess the accuracy of these formulae by discrimination and/or calibration. Results After searching several databases, only one study was eligible for inclusion in the review. This study of 2300 Chinese individuals with IgAN had a median follow-up of 2.5 years. Two-hundred eighty-eight individuals had a composite outcome of 50% decline in eGFR or ESRD, and 214 individuals developed ESRD. Both the KFRE and the IgAN Risk Prediction (IRP) tool (incorporating the OC) were highly accurate at predicting ESRD with a C-statistic of 0.90 and 0.91, respectively. Subgroup analysis demonstrated improved performance of IRP over KFRE in discrimination for individuals with preserved eGFR (> 60 ml/min/1.73 m2) at baseline. The risk of bias was high due to insufficient follow-up and handling of missing data, so overall confidence in findings is very low. Conclusion There is currently insufficient evidence to compare the accuracy of the KFRE and OC in determining outcomes in IgAN. Further research is required in this field. Systematic review registration PROSPERO CRD42022364569.